Siak Tourism Based on Environmental Policy: Analysis of Tourism Development Opportunities and Challenges - Pakhapan Saiman; Heriyanto Meyzi; Ismandianto Ismandianto; Marta Auradian; Wirman Welly; Mashur Dadang; Fadli Mashur (E3S Web of Conferences)
This research seeks to examine various environmentally based international tourism developments with investment policies in Siak Regency, Riau Province, Indonesia. This research aims to identify, map international tourism opportunities and solutions specifically for tourism in Siaknegara district. Research data was collected based on observations, interviews and documentation in the field. Once collected, the data is analyzed by SWOT analysis. The research results show the need to make strategic formulations in order to develop internationally so that it is sustainable. The government’s policy of developing international border tourism for various stakeholders to collaborate has not been well integrated between the central government and the local government. The focus point for Siak tourism development is basic infrastructure and public facilities so that it is hoped that it will continue to increase the value and competitiveness of international border tourism. Siak tourism has the tagline “The Homeland of Malay”. All tourism activities must consider the existence of existing ecosystems in order to preserve existing life and maintain environmental quality. The need for policies and strategies in environmentally based management of natural tourism aims to preserve the environment and maintain the continuity of natural tourism activities so as to increase the country’s foreign exchange.